PERANCANGAN MUROTTAL OTOMATIS MENGGUNAKAN MIKROKONTROLLER ARDUINO MEGA 2560 - Jauhari Arifin; Leni Natalia Zulita; Hermawansyah Hermawansyah (Jurnal Media Infotama, 2016)
The research Scheme of Automatic Murottal Use Microkontroller Arduino Mega 2560 designed to facilitate work of custodian of mosque when seedang not residing in place so that when time of sholat have almost arrive hence appliance of ni can turn around holy sentence bouncing movement Al Qu'An automatically. Research Laboratory of Hardware Study Program Computer Engineering Faculty Computer Science University of Dehasen Bengkulu, In July - September 2015. Data method which used in this research Method Documentation, Observation, and Study Book.Result of from this research obtained Conclusion that is automatic murottal can use Application Ianguage of Program Visual Basic 6.0 can be by 2 the way of that is: Automatically and Manual, Automatically by chosening letter to turning around and lead the time twiddling before adzan fill the air, while manually will be controlled to Application appearance with clicking one of the button exist in application of interface computer.Keyword: Real Time Clock (RTC), Microkontroller Arduino Mega 2560, Ianguage of Visual Basic 6.0 program